Sufism and Disease Healing: (A case study of Zikr activities at Majelis Zikir La Ilaha Illalah and Majelis Makrifat in Makassar City) - Tahir, Gustia (Tumanurung: Jurnal Sejarah dan Budaya, 2024)
Humans are creatures that consist of physical and spiritual. The two have a very strong bond and influence each other. The body needs food, so is the spirit. Therefore, good spirituality affects physical health, otherwise poor health can also affect mental health. This research wants to know how zikir affects physical health, also wants to know the model of zikir activities carried out by members of the zikir group. This research takes two groups of zikir in the city of Makassar. Data collection techniques were carried out in in-depth interviews with 10 informan of each group. In addition, interviews with the board of zikir were also conducted. The results of research show that there is a very positive correlation between zikir activity and physical health. The zikir activity that is done must be regular and practiced in sincere motivation and wanting to get closer to Allah. This research recommends the community to actively participate in or carry out zikir activities. The government and medical parties is to create a zikir curriculum in hospitals to speed up patient recovery.